Saberes docentes sobre o tema Função: uma investigação das praxeologias - Rossini, Renata (2006)
The issues of this research are the conceptions and difficulties of a group of teachers regarding the function concept, and how they overcame them along a continuous formation process. Although there are some studies regarding the students' difficulties and possible obstacles to the teaching and learning of this theme, it is necessary to pay attention on what a formative action means to a group of primary and middle school teachers, since there are not many researches involving teachers. Therefore, this thesis answers to the following questions: Which mathematical organizations are mobilized during the construction of a teaching sequence on functions for an 8th grade of Middle Education? How do the teachers build or rebuild their teacher knowledge on the function concept? The adopted methodology used an action-research as a collaborative investigation, because it propitiates the interaction between the researcher and the teachers and their practice in formation and in action. The theoretical foundation was based on the Anthropological Theory of the Didactic of Chevallard (1999) to model the function concept as Mathematical Organization and Didactic Organization associated with function conceptions such as magnitude interdependence, in and out machine, analytical expression, pattern of regularity of geometric sequences and correspondence between sets. This foundation granted the analysis of some 8th grade mathematics books and teachers' production along a process of continuous formation. As the teachers build the didactic organizations by preparing a didactic sequence for the function teaching and learning for an 8th grade class, they analyse and rebuild their own knowledge on function. At the end, the teachers manage to get relative articulation between the mobilized organizations, and it allow them to innovate and create new exercises. Building a teaching sequence and following its applications in classrooms made the teachers look at their students more positively and also feel more valued at their work